Endobiont Viruses Sensed by the Human Host – Beyond Conventional Antiparasitic Therapy - Fichorova, Raina N.; Lee, Yujin; Yamamoto, Hidemi S.; Takagi, Yuko; Hayes, Gary R.; Goodman, Russell P.; Chepa-Lotrea, Xenia; Buck, Olivia R.; Murray, Ryan; Kula, Tomasz; Beach, David H.; Singh, Bibhuti N.; et al. (PloS one, 2012)
Wide-spread protozoan parasites carry endosymbiotic dsRNA viruses with uncharted implications to the human host. Among them, Trichomonas vaginalis, a parasite adapted to the human genitourinary tract, infects globally ∼250 million each year rendering them more susceptible to devastating pregnancy complications (especially preterm birth), HIV infection and HPV-related cancer. While first-line antibiotic treatment (metronidazole) commonly kills the protozoan pathogen, it fails to improve reproductive outcome. We show that endosymbiotic Trichomonasvirus, highly prevalent in T. vaginalis clinical isolates, is sensed by the human epithelial cells via Toll-like receptor 3, triggering Interferon Regulating Factor -3, interferon type I and proinflammatory cascades previously implicated in preterm birth and HIV-1 susceptibility. Metronidazole treatment amplified these proinflammatory responses. Thus, a new paradigm targeting the protozoan viruses along with the protozoan host may prevent trichomoniasis-attributable inflammatory sequelae.